Optimized regression model for microhardness of experimental dental composite resins with nano-hydroxyapatite filler particles - Chaitali Keshav Mirajkar; Jasmin Winnier; Umesh Hambire (Wolters Kluwer Medknow Publications, 2023)
Background: Bioactive materials produce a biological reaction such as stimulation of pulpal cells for dentinal repair and induction of the formation of hydroxyapatite. Aim: The study was conducted to evaluate the microhardness of experimental dental composite resins (EDCR) containing nano-hydroxyapatite, zirconia, and glass filler particles. Materials and Methods: The EDCR was prepared with varying concentrations of barium aluminum fluoride glass (5-20 nm), zirconia (4-11 nm), and hydroxyapatite (20-80 nm) filler particles added to the organic matrix. The L9 orthogonal array was used to prepare a sample size of 27 samples. Disc-shaped specimens of 10 mm diameter and 4 mm thickness were prepared using the American Society for Testing and Materials E384 standard for testing the microhardness. The Taguchi's method of optimization was used to obtain a composite with optimum microhardness. A regression model was developed. Results: EDCR with 23.7% of zirconia, 27.5% of nano-hydroxyapatite, and 20% of glass filler particles gave the optimum microhardness of 222.67 HV. The confirmatory experimental test of EDCR gave a microhardness of 225 HV. The model developed with regression equation for the microhardness was 60-123 Z + 114 H + 17.8 G + 2.48 ZH − 0.02 HG + 0.97 Z2 − 3.40 H2. The difference between the R2 (99.9) and adjusted R2 values (99.4) is <0.5, this shows that the model is acceptable. Conclusion: The EDCR developed after using Taguchi's method of optimization had microhardness superior to that of the commercially available composite resins.